Resiliencia y satisfacción laboral en los profesionales de la Salud de los Subcentros de la ciudad de Babahoyo - Laje Valencia, Lucrecia Abigail (2025)
This study analyzes the influence of resilience on job satisfaction among healthcare professionals in the health centers of Babahoyo. A correlational, non-experimental, and cross-sectional approach was used to assess resilience levels and job satisfaction concerning tasks, rewards, and the work environment. The results indicate that resilience is a key factor in workplace well-being, with significant differences between specialties. Physicians and nurses exhibited higher resilience levels, likely due to their training and experience, whereas health technicians and administrative staff showed lower levels, making them more vulnerable to work-related stress. Additionally, aspects such as recognition, task quality, and a favorable work environment directly impact job satisfaction. The moderate positive correlation between resilience and job satisfaction suggests that a stronger capacity for adaptation and coping translates into greater professional well-being. These findings highlight the importance of enhancing resilience through strategies such as support networks, emotional skills training, and stress management. In conclusion, the study emphasizes the need to integrate organizational measures that promote healthier work environments, directly impacting professional performance and the quality of care provided to patients.